2018
DOI: 10.1111/jcpp.12889
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic risk, parenting, and inhibitory control in early childhood: the role of respiratory sinus arrhythmia

Abstract: These results suggest that higher levels of RSAB may mitigate the influence of environmental risk on the development of inhibitory control early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
1
17
1
5
Order By: Relevance
“…These findings corroborate recent research findings demonstrating the presence of differential susceptibility in the relationship between family adversity and socioemotional outcomes (e.g., Obradović, Bush, Stamperdahl, Adler, & Boyce, 2010; Sturge-Apple, Suor, Davies, Cicchetti, & Rogosch, 2016). It should be noted that some previous studies testing differential susceptibility models with respect to early caregiving and children's development are inconsistent with the findings of the present study (e.g., Holochwost, Volpe, Gueron-Sela, Propper, & Mills-Koonce, 2018). For example, Gueron-Sela et al (2017) found that the moderating effect of children's resting RSA on early caregiving and executive functioning was consistent with the diathesis-stress not the differential susceptibility model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate recent research findings demonstrating the presence of differential susceptibility in the relationship between family adversity and socioemotional outcomes (e.g., Obradović, Bush, Stamperdahl, Adler, & Boyce, 2010; Sturge-Apple, Suor, Davies, Cicchetti, & Rogosch, 2016). It should be noted that some previous studies testing differential susceptibility models with respect to early caregiving and children's development are inconsistent with the findings of the present study (e.g., Holochwost, Volpe, Gueron-Sela, Propper, & Mills-Koonce, 2018). For example, Gueron-Sela et al (2017) found that the moderating effect of children's resting RSA on early caregiving and executive functioning was consistent with the diathesis-stress not the differential susceptibility model.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Gueron-Sela et al (2017) found that the moderating effect of children's resting RSA on early caregiving and executive functioning was consistent with the diathesis-stress not the differential susceptibility model. Further, Holochwost et al (2018) found that resting RSA, not parenting, moderated cumulative risk exposure on children's inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Family SES and parental behaviors are shown to be predictors of IC in youth [20][21][22][23][24]. In a study on 147 7-10-year-old children, Cabello et al investigated the relationship between parental educational attainment and youth IC as well as aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate general linear modelling (MGLM) analyses were conducted to examine the associations between the two dimensions of self‐regulation and RSA in the same model. Preliminary analyses were carried out including child age, sex, race/ethnicity as covariates because they have been associated with RSA or self‐regulation outcomes in the literature (El‐Sheikh, 2005; Holochwost, Volpe, Gueron‐Sela, Propper, & Mills‐Koonce, 2018). However, none were significant.…”
Section: Resultsmentioning
confidence: 99%
“…With a larger sample, the effects of race/ethnicity and other demographic factors like socio‐economic status (SES) on RSA and self‐regulation could be examined. They are particularly important areas of future work because there is a lack of physiology research with ethnic minority populations and because sociodemographic risk can influence children’s inhibitory control and self‐regulation competencies (Evans & Rosenbaum, 2008; Holochwost et al, 2018). Recent studies have suggested that cultural and social factors shape the meaning of RSA and its relative contributions to outcomes (Keen, Turner, Mwendwa, Callender, & Campbell, 2015; Sturge‐Apple et al, 2016).…”
Section: Discussionmentioning
confidence: 99%